2007
DOI: 10.1007/s10551-007-9469-2
|View full text |Cite
|
Sign up to set email alerts
|

Values Versus Regulations: How Culture Plays Its Role

Abstract: regulation, entry, culture, economic development, corruption, time,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Generally, such studies suggest that corruption stems from a lack of capitalism and inadequate pay for government employees. However, consistent with the findings of Jing and Graham (2008) we have excluded a connection between consumer resources and corruption levels in our model specification. That is, they found that the correlation between corruption and economic development disappeared when cultural values were modeled as influencing both.…”
Section: Relationship-oriented Cultures and Consumer Resourcessupporting
confidence: 80%
See 2 more Smart Citations
“…Generally, such studies suggest that corruption stems from a lack of capitalism and inadequate pay for government employees. However, consistent with the findings of Jing and Graham (2008) we have excluded a connection between consumer resources and corruption levels in our model specification. That is, they found that the correlation between corruption and economic development disappeared when cultural values were modeled as influencing both.…”
Section: Relationship-oriented Cultures and Consumer Resourcessupporting
confidence: 80%
“…The complexity of corruption results in current definitions which are fraught with subjectivity and cultural relativism (Houston and Graham, 2001); it is evident that people from different countries have various perceptions and tolerances toward bribery even though it is illegal in most nations (Jing and Graham, 2008). Donleavy et al (2008) suggest that in China, corruption has three faces: tanwu (malpractice), whui (bribery), and tequan (privileges).…”
Section: Toward a Richer Definition Of Corruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence indicates that culture matters in responsible leadership and ethical behavior, but how, when, and why are less clear. For instance, past research has found significant cultural differences in managers' willingness to accept bribery as the price of business, and willingness to engage in other forms of unethical conduct (e.g., Jing and Graham 2008;Martin et al 2007). However, as culture is often correlated with other socio-economic influences such as GDP and institutions, it is difficult to determine which country-level factors are driving corrupt behavior.…”
Section: Limitations and Implications For Researchmentioning
confidence: 99%
“…While the index has been used a large number of times as an independent variable, far less work has gone into explaining economic freedom. Recent scholarly work has examined the impact of foreign aid (Bearce and Tirone 2010), personal characteristics of politicians (Dreher et al 2009), and culture (Jing and Graham 2008) on economic freedom as measured by the EFW index. Inequality too may play a role in determining economic freedom.…”
Section: Ryan H Murphymentioning
confidence: 99%